2011
DOI: 10.1371/journal.ppat.1002336
|View full text |Cite
|
Sign up to set email alerts
|

Murine Gamma Herpesvirus 68 Hijacks MAVS and IKKβ to Abrogate NFκB Activation and Antiviral Cytokine Production

Abstract: Upon viral infection, mitochondrial antiviral signaling (MAVS) protein serves as a key adaptor to promote cytokine production. We report here that murine gamma herpesvirus 68 (γHV68), a model virus for oncogenic human gamma herpesviruses, subverts cytokine production via the MAVS adaptor. During early infection, γHV68 hijacks MAVS and IKKβ to induce the site-specific phosphorylation of RelA, a crucial subunit of the transcriptionally active NFκB dimer, which primes RelA for the proteasome-mediated degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 55 publications
3
51
0
Order By: Relevance
“…We found that IKKe, when activated by kGPCR, phosphorylated RelA at Ser468 and promoted its nuclear translocation, agreeing with the findings that RelA Ser468p up-regulates the expression of a subset of inflammatory genes (32). Interestingly, previous reports, including our findings from virus-infected cells (37), showed that the Ser468 phosphorylation primes RelA for degradation (38,39). By contrast, kGPCR expression activates IKKe that phosphorylates and activates RelA.…”
Section: Discussionsupporting
confidence: 91%
“…We found that IKKe, when activated by kGPCR, phosphorylated RelA at Ser468 and promoted its nuclear translocation, agreeing with the findings that RelA Ser468p up-regulates the expression of a subset of inflammatory genes (32). Interestingly, previous reports, including our findings from virus-infected cells (37), showed that the Ser468 phosphorylation primes RelA for degradation (38,39). By contrast, kGPCR expression activates IKKe that phosphorylates and activates RelA.…”
Section: Discussionsupporting
confidence: 91%
“…Murine ␥-herpesvirus (gamma-HV68), a model system for KSHV and EBV, is known to activate IKK-␤. Interestingly, activated, phosphorylated IKK-␤ promotes viral replication, because the viral protein RTA (replication and transcription activator) is a phosphorylation target for IKK-␤ kinase activity (49). In contrast to this situation, in the case of vaccinia virus infection, the viral protein B14 modulates IKK-␤ kinase activity in a way that inhibits the phosphorylation of its downstream target IB␣ without exerting any influence on IKK-␣ activity (50,51).…”
Section: Mice a Infarmentioning
confidence: 99%
“…6). The lytic transactivator RTA has been reported to inhibit multiple cell signaling pathways, including the TLR, MAVS, and NF-B signaling pathways (63)(64)(65). However, the reduction in IL-1␤ at 9 hpi did not require RTA or RTA-dependent viral genes.…”
Section: Discussionmentioning
confidence: 90%
“…Mutations in MHV68 orf50 severely limit viral gene expression and block virus replication (30,62). RTA has additional functions in host signaling pathways, including the degradation of NF-B signaling proteins, impairment of cytokine production, and interference with TLR signaling (63)(64)(65). To examine whether RTA or RTA-dependent gene expression drives suppression of IL-1␤, we infected BMDMs with a recombinant MHV68-ORF50stop virus (30) prior to LPS and ATP treatment and evaluated the intracellular and secreted levels of IL-1␤ at 9 hpi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation